Pharmacy Students' Informal Use of Facebook and its Perceived Role in Pharmacy Education in Jordan - Zeinab Al Subeh; Feras Alali; Ahmed Awaisu (University of Minnesota Libraries Publishing, 2018)
Objectives: The use of social media, including Facebook, as a tool for learning is becoming increasingly important in health professional education programs including pharmacy. This study aimed to evaluate undergraduate pharmacy students' informal use and attitudes toward Facebook in professional pharmacy education in Jordan. Methods: This study was a cross-sectional web-based survey using a 38-item questionnaire that was developed through a multi-phase iterative process. The study targeted all professional year pharmacy students, both BSc and PharmD, at Jordan University of Science and Technology (JUST). Results: Seven hundred twenty pharmacy students responded to the survey (response rate 31.3%). The majority of the students (98.8%) had personal accounts on Facebook. Of this, the majority (82.4%) reported that they unofficially used Facebook as a tool for studying or academic purposes beside other social purposes. Overall, the students demonstrated positive attitudes toward the use of Facebook in pharmacy education. About 78.6% of the respondents reported that Facebook contributed to their academic success. Furthermore, a substantial proportion of the students found Facebook well acceptable in teaching and learning environment (55.2%) and believed that pharmacy schools should formally encourage students to use Facebook for academic purposes (54.1%). Conclusion: The findings of this study suggest that pharmacy students in Jordan frequently and highly utilize Facebook as an unofficial tool for communication, teaching and learning. Pharmacy schools should make every effort to create appropriate learning environment within Facebook that could positively impact students' academic success. Interventions to improve attitudes toward social media e-professionalism should be in place before formally implementing Facebook and other social media platforms within the pharmacy academic environment. Conflict of Interest We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties. Treatment of Human Subjects: IRB review/approval required and obtained   Type: Original Research